2012
DOI: 10.1002/ijc.27930
|View full text |Cite
|
Sign up to set email alerts
|

PITX2: A promising predictive biomarker of patients' prognosis and chemoradioresistance in esophageal squamous cell carcinoma

Abstract: The paired-like homeodomain transcription factor 2 (PITX2), a downstream effector of wnt/b-catenin signaling, is well known to play critical role during normal embryonic development. However, the possible involvement of PITX2 in human tumorigenesis remains unclear. In this study, we extend its function in human esophageal squamous cell carcinoma (ESCC). The real-time PCR, Western blotting and immunohistochemistry (IHC) methods were applied to examine expression pattern of PITX2 in two different cohorts of ESCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…We recently found that PITX2 was frequently upregulated in ESCC tissues, as compared with the normal epithelial tissue. Furthermore, overexpression of PITX2 was correlated with poor prognosis and/or radiochemoresistance of the disease (12). Clearly, a better understanding of the tumor-specific regulation of PITX2 and the targets it regulates is crucial and has potentially important clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…We recently found that PITX2 was frequently upregulated in ESCC tissues, as compared with the normal epithelial tissue. Furthermore, overexpression of PITX2 was correlated with poor prognosis and/or radiochemoresistance of the disease (12). Clearly, a better understanding of the tumor-specific regulation of PITX2 and the targets it regulates is crucial and has potentially important clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The specific sequence of the shRNA targeting FRAT1 was designed as previously described (19)(20)(21)(22) using the following primer sequences: Forward, 5'-GCA GTT ACG TGC AAA GCT TTT CAA GAG AAA GCT TTG CAC GTA CTGC-3' and reverse, 3'-CGT CAA TGC ACG TTT CGA AAA GTT CTC TTT CGA AAC GTG CAT TGA CG-5'. The shRNA template was then added to two endonucleases, HindIII and BamH1, for digestion.…”
Section: Reverse Transcription Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…The variations in clinical responses to CRT are most evident for esophageal squamous cell carcinoma (ESCC), and the survival rates between responders and non-responders are quite different even with the same clinical stage (5,6). Therefore, there is a compelling need to identify novel biomarkers that hold promise of precisely predicting tumor response to CRT to tailor treatments for different ESCC patients and enhance survival (7).…”
Section: Introductionmentioning
confidence: 99%